Medium- to long-term health condition of patients post-COVID-19, exercise intolerance and potential mechanisms: A narrative review and perspective - Fabian Schwendinger; Denis Infanger; Debbie J Maurer; Thomas Radtke; Justin Carrard; Julia M Kröpfl; Aglaia Emmenegger; Henner Hanssen; Christoph Hauser; Udo Schwehr; Hans H Hirsch; Julijana Ivanisevic; et al. (SAGE Open Medicine)
Background: Patients recovering from COVID-19 often present with impaired health and persisting symptoms such as exercise intolerance ⩾3 months post-infection. Uncertainty remains about long-term recovery. We aimed to review studies examining cardiac function, macro- or microvascular function, blood biomarkers and physical activity in adult patients post-COVID-19 and highlight current knowledge gaps. Results: Using echocardiography, persistent cardiac involvement of the left ventricle was observed in a fraction of patients both hospitalized and non-hospitalized. Ventricular dysfunction was often subclinical but may partly contribute to exercise intolerance post-COVID-19. Endothelial dysfunction was seen on micro- and macrovascular levels using retinal vessel imaging methods and brachial artery flow-mediated dilation, respectively. Studies reporting blood biomarkers of disease-specific impairment and endothelial dysfunction yielded upregulated inflammation, hypercoagulability, organ and endothelial damage up to several months after infection. Omics’ scale lipid profiling studies provide preliminary evidence of alterations in several lipid subspecies, mostly during acute COVID-19, which might contribute to subsequent endothelial and cardiometabolic dysfunction. Yet, more robust evidence is warranted. Physical activity may be reduced up to 6 months post-COVID-19. However, studies measuring physical activity more precisely using accelerometry are sparse. Overall, there is growing evidence for long-term multiple organ dysfunction. Conclusion: Research combining all the above methods in the search for underlying mechanisms of post-COVID-19 symptoms is mostly missing. Moreover, studies with longer follow-ups (i.e. ⩾18 months) and well-matched control groups are lacking. The findings may aid the development of rehabilitation regimes for post-COVID-19 syndrome. Condensed abstract This review examined cardiac function, vascular function, blood biomarkers and physical activity in patients post-COVID-19. Evidence suggests long-term dysfunction in multiple organ systems and exercise intolerance due to various factors, including endothelial damage and, in some patients, subclinical ventricular dysfunction. We highlight knowledge gaps for further research to aid post-COVID-19 rehabilitation.